2007
DOI: 10.1007/s12263-007-0073-y
|View full text |Cite
|
Sign up to set email alerts
|

Schisandra fructus extract ameliorates doxorubicin-induce cytotoxicity in cardiomyocytes: altered gene expression for detoxification enzymes

Abstract: The effect of Schisandra fructus extract (SFE) on doxorubicin (Dox)-induced cardiotoxicity was investigated in H9c2 cardiomyocytes. Dox, which is an antineoplastic drug known to induce cardiomyopathy possibly through production of reactive oxygen species, induced significant cytotoxicity, intracellular reactive oxygen species (ROS), and lipid peroxidation. SFE treatment significantly increased cell survival up to 25%, inhibited intracellular ROS production in a time-and dosedependent manner, and inhibited lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 25 publications
(22 reference statements)
4
9
0
Order By: Relevance
“…The observed GSH deficiency and elevated GSSG levels in the DOX group might be due to GSH consumption in the interactions of DOX‐induced free radicals with bio‐membrane and the subsequent lipid peroxidation. Clearly, these data indicate the occurrence of oxidative stress, which is in accordance with reports of previous studies . Pre‐treatment of H9c2 cells with sesamol significantly guarded against the oxidative stress observed in the DOX group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The observed GSH deficiency and elevated GSSG levels in the DOX group might be due to GSH consumption in the interactions of DOX‐induced free radicals with bio‐membrane and the subsequent lipid peroxidation. Clearly, these data indicate the occurrence of oxidative stress, which is in accordance with reports of previous studies . Pre‐treatment of H9c2 cells with sesamol significantly guarded against the oxidative stress observed in the DOX group.…”
Section: Discussionsupporting
confidence: 92%
“…Clearly, these data indicate the occurrence of oxidative stress, which is in accordance with reports of previous studies. [63,64] Pretreatment of H9c2 cells with sesamol significantly guarded against the oxidative stress observed in the DOX group.…”
Section: Discussionmentioning
confidence: 95%
“…Clearly, these data indicate the occurrence of oxidative stress, which is in accordance with reports of previous studies [32,33]. The reduced GSH and the elevated GSSG levels in the DOX group might be due to GSH consumption in the interactions of DOX-induced free radicals with bio-membrane and the subsequent lipid peroxidation.…”
Section: Discussionsupporting
confidence: 92%
“…So far, very little and rather variable data are available regarding HO1 and ANT cardiotoxicity, and virtually nothing has been reported regarding the clinically relevant chronic forms resulting in heart failure. Using proliferating H9c2 cells, a suppression of HO1 expression has been reported after in vitro ANT treatment (Bernuzzi et al, 2009), whereas others have suggested the opposite in a microarray study (Choi et al, 2008). Little to no change in HO1 expression has been seen at protein and mRNA levels 2 weeks after a single supratherapeutic ANT dose (Suliman et al, 2007) and 70 days after injection of 1 mg/kg for 10 days (Richard et al, 2011), respectively.…”
Section: Discussionmentioning
confidence: 99%